PENINGKATAN KOMPETENSI PAMONG BELAJAR SEBAGAI AGEN PEMBERDAYAAN MASYARAKAT MELALUI JALUR PENDIDIKAN NONFORMAL - Rasid Rasid (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
Non-formal education provides various kinds of educational services to improve the quality of human resources in Indonesia. The teachers and education personnel in non-formal education play a very important role to reach the educational goals. In implementing the non-formal education program, tutors act as front liners and simultanously they also function as the agents empowering the communitites. A tutors functions non only as a teacher, but also as a change agent and information source for the learning communities. To complete their tasks, this article thinks the urgent needs to improve the tutors’ competence. Quoting the tutors’ competence lists identified by The Standardization Board of National Education, this article discusses the possible efforts to improve the tutors’ competence to enable the to perform their tasks including to community empowering.